The road to a world-unified approach to the management of patients with gastric intestinal metaplasia: a review of current guidelines - Dinis-Ribeiro, M; Shah, S; El-Serag, H; Banks, M; Uedo, N; Tajiri, H; Coelho, LG; Libanio, D; Lahner, E; Rollan, A; Fang, J; Moreira, L; et al. (BMJ Publishing Group, 2024)
Objective: During the last decade, the management of gastric intestinal metaplasia (GIM) has been addressed by several distinct international evidence-based guidelines. In this review, we aimed to synthesise these guidelines and provide clinicians with a global perspective of the current recommendations for managing patients with GIM, as well as highlight evidence gaps that need to be addressed with future research. Design: We conducted a systematic review of the literature for guidelines and consensus statements published between January 2010 and February 2023 that address the diagnosis and management of GIM. Results: From 426 manuscripts identified, 16 guidelines were assessed. There was consistency across guidelines regarding the purpose of endoscopic surveillance of GIM, which is to identify prevalent neoplastic lesions and stage gastric preneoplastic conditions. The guidelines also agreed that only patients with high-risk GIM phenotypes (eg, corpus-extended GIM, OLGIM stages III/IV, incomplete GIM subtype), persistent refractory Helicobacter pylori infection or first-degree family history of gastric cancer should undergo regular-interval endoscopic surveillance. In contrast, low-risk phenotypes, which comprise most patients with GIM, do not require surveillance. Not all guidelines are aligned on histological staging systems. If surveillance is indicated, most guidelines recommend a 3-year interval, but there is some variability. All guidelines recommend H. pylori eradication as the only non-endoscopic intervention for gastric cancer prevention, while some offer additional recommendations regarding lifestyle modifications. While most guidelines allude to the importance of high-quality endoscopy for endoscopic surveillance, few detail important metrics apart from stating that a systematic gastric biopsy protocol should be followed. Notably, most guidelines comment on the role of endoscopy for gastric cancer screening and detection of gastric precancerous conditions, but with high heterogeneity, limited guidance regarding implementation, and lack of robust evidence. Conclusion: Despite heterogeneous populations and practices, international guidelines are generally aligned on the importance of GIM as a precancerous condition and the need for a risk-stratified approach to endoscopic surveillance, as well as H. pylori eradication when present. There is room for harmonisation of guidelines regarding (1) which populations merit index endoscopic screening for gastric cancer and GIM detection/staging; (2) objective metrics for high-quality endoscopy; (3) consensus on the need for histological staging and (4) non-endoscopic interventions for gastric cancer prevention apart from H. pylori eradication alone. Robust studies, ideally in the form of randomised trials, are needed to bridge the ample evidence gaps that exist.